Emotion representation for virtual environments - Karpouzis, Kostas; Raouzaiou, Amaryllis; Tsapatsoulis, Nicolas; Kollias, Stefanos D. (My University, 2003)
Research on networked applications that utilize multimodal information about their users' current emotional state are presently at the forefront of interest of the computer vision and artificial intelligence communities. Human faces may act as visual interfaces that help users feel at home when interacting with a computer because they are accepted as the most expressive means for communicating and recognizing emotions. Thus, a lifelike human face can enhance interactive applications by providing straightforward feedback to and from the users and stimulating emotional responses from them. Thus, virtual environments can employ believable, expressive characters since such features significantly enhance the atmosphere of a virtual world and Communicate messages far more vividly than any textual or speech information. In this paper, we present an abstract means of description of facial expressions, by utilizing concepts included in the MPEG-4 standard. Furthermore, we exploit these concepts to synthesize a wide variety of expressions using a reduced representation, suitable for networked and lightweight applications.
Keywords: Emolional representation; MPEG-4; Networked virtual environmenls; Avatars; Expression synthesis